2022
DOI: 10.1097/cce.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acute Kidney Injury During Invasive Mechanical Ventilation and ICU Outcomes and Respiratory System Mechanics

Abstract: OBJECTIVES: Compare ICU outcomes and respiratory system mechanics in patients with and without acute kidney injury during invasive mechanical ventilation. DESIGNS: Retrospective cohort study. SETTINGS: ICUs of the University of California, San Diego, from January 1, 2014, to November 30, 2016. PATIENTS: Five groups of patients were compared based on the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…In this study, 184(58.0%) of the study participants were male, of which 76(41.3%) of them developed Acute Kidney Injury [ 32 ] whereas 133(39.1%) female participants developed AKI during their ICU stay. The mean age of the study participants was 54.4 years (SD ±18.19356) with a minimum of 19 years and a maximum of 97 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 184(58.0%) of the study participants were male, of which 76(41.3%) of them developed Acute Kidney Injury [ 32 ] whereas 133(39.1%) female participants developed AKI during their ICU stay. The mean age of the study participants was 54.4 years (SD ±18.19356) with a minimum of 19 years and a maximum of 97 years.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, invasive mechanical ventilation is attributed to the clinical consequences that lead to altered renal hemodynamics [ 47 ]. This leads to hypo perfusion to the kidney tissue due to low cardiac output that impaired venous return and leads to ischemic injury that is termed acute renal tubular necrosis [ 32 ]. Finally, this leads to a decline in glomeruli filtration rate and elevation of serum creatinine causing the sign of Acute Kidney Injury.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, DP has been shown to be the best ventilator parameter for predicting mortality in ARDS, and higher DP has also been associated with AKI. 21 , 22 Secondly, in a recent study, patients with non-recovery of AKI were associated with severe ARDS, which explains that the DRONE score encompassing poorer oxygenation can predict AKI subphenotype 2. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Apart from these, literature shows that shock and comorbid illnesses like hypertension and malignancy are associated with non-recovery of AKI in ARDS patients. 22 It is notable, that co-morbid illnesses are part of the calculation of DRONE score as well since it incorporates APACHE II and mNUTRIC score. Likewise, the presence of shock is incorporated in the SOFA score used for calculation of the DRONE score.…”
Section: Discussionmentioning
confidence: 99%
“…In the ARDSnet study, the 180-day mortality rate was much higher in those who had AKI compared to those who did not develop this complication (58% and 28%, respectively) [8]. One retrospective study demonstrated an increase in the number of days of artificial lung ventilation (ILV) (10 vs. 7 days) and the duration of switching to independent breathing (41 vs. 21 hours) in patients with ARDS complicated by AKI compared to ARDS alone [11]. A. Panitchote et al [12] concluded that two-thirds of patients with ARDS developed AKI during intensive care, and almost half of these patients progressed to stage III of AKI according to the Kidney Disease: Improving Global Outcomes (KDIGO) classification.…”
mentioning
confidence: 99%